Strengthening Malay women entrepreneurship through business intelligent - Fuad, Nurwahida; Bohari, Abdul Manaf (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
In general, the development of women entrepreneurship, as well as important to other business sector, has been growing rapidly in Malaysia. The significant importance of women entrepreneurship especially Malay women entrepreneurship to the growth of overall Malaysia‟s economy is proved by the variety of initiatives, policies and organization that established for women entrepreneurs. These are including venture capital, financial funding, training, physical infrastructure such as entrepreneur incubator and laboratory, business consultant, an organization of National Women Entrepreneurs, USAHANITA's, and so on. However, contribution of Malay women entrepreneur is still not really discussed intensively and to the best of knowledge, the improvement of business performance has not tested well because of some issues and challenges in the marketplace. Thus, the main objective of this paper is discussing the challenges that faced by Malay women entrepreneur such as identified as local and global based issues. Thus, the need to strengthening Malay women entrepreneur competitive level is a vital important to fostering the greater capacity of them, especially for achieved global standard of technological and innovation. Strategically, this paper is focused on business intelligent resources as information technology strategy for strengthening Malay women entrepreneurs' to positioning them into competitive advantages on the marketplace. Business intelligent is not really explored to apply in contact of Malay women entrepreneur strategy because of some limitations. Finally, some aspect of information strategy planning is discussed for establish business intelligent within Malay women entrepreneur firms, because key success factors of business intelligent implementation in started from strategy planning point of view.